Drinking water quality impacts oocyte viability and embryo development - Winstanley, Yasmyn E.; Gonzalez, Macarena B.; Andreas, Eryk; Connaughton, Haley; Bergen, Jean; Ween, Miranda; Russell, Darryl L.; Shearer, Cameron J.; Robertson, Sarah A.; Robker, Rebecca L. (Frontiers in Reproductive Health, 2024)
Normal reproductive function and fertility is considered a “sixth vital sign” because disruptions to this sensitive physiological system can forewarn other health issues, including exposure to environmental toxicants. We found that female mice exhibited profound loss of embryos during pre-implantation and fetal development coincident with a change to the source of their drinking water. When female mice were provided with tap water from the building in which they were housed (Water 2), instead of tap water from a neighboring building which was their previous supply (Water 1), ovulated oocytes were degenerated or had impaired meiotic maturation, and failed to form embryos. The harmful effects of Water 2 exposure were not reversible even following a recovery period; however, carbon-filtration of Water 2 removed the toxic contaminant. Water composition analysis to identify the responsible toxicant(s) found that trace elements were present at expected levels and phthalates were undetectable. Per- and Poly-fluoroalkyl Substances (PFAS), a family of persistent organic pollutants were detected at ∼4 ng/L. To investigate further, female mice were given drinking water categorized by level of PFAS contamination (0.6 ng/L, 2.8 ng/L, or 4.4 ng/L) for 9 weeks. Compared to mice consuming purified MilliQ water, mice consuming PFAS-contaminated water had decreased oocyte quality, impaired embryogenesis and reduced cell numbers in blastocysts. PFAS concentration in the drinking water was negatively correlated with oocyte viability. Importantly, the levels of PFAS detected in the tap water are within current “safe level” guidelines, and further research is needed to determine whether PFAS are responsible for the observed reproductive toxicity. However, this research demonstrating that water deemed suitable for human consumption has detrimental effects on mammalian embryo development has important implications for public health and water quality policies.